An update on the development of novel antifungal agents for eumycetoma - Chandler, David J.; Bonifaz, Alexandro; van de Sande, Wendy W. J. (Frontiers in Pharmacology, 2023)
Eumycetoma, a chronic subcutaneous mycosis, responds poorly to the available antifungal treatments and patients often require extensive surgical resection or amputation of the affected limb. More effective treatments are needed for eumycetoma. This article will describe some of the approaches being used to develop and evaluate new treatments for eumycetoma, summarise the latest developments and discuss the challenges that lie ahead.